Desain dan Uji Coba Media Motion Comic Berbasis SETS (Science, Environment, Technology, Society) pada Materi Asam Basa - Lisa Utami; Uci Nornasari1 (UIR Press, 2022)
This research aimed at designing SETS (Science, Environment, Technology, Society) based Motion Comic media on Acid Base lesson valid based on the validation by the experts of material and media, teacher practicality and student response. It was R&D (Research and Development) with 4-D development model. It was conducted at State Senior High School 01 Kampar Kiri Tengah to the eleventh-grade students of Natural Science 3. Motion Comic media could be stated proper, if it completed the valid and practical aspects. Validity could be seen from the result of validation by using validation sheet. The validation result percentage by the expert of material overall was 92.22% with very valid criterion. The validation result percentage by the expert of media overall was 82.85% with very valid criterion. Teacher practicality test was conducted to 2 teachers, and the result was 85.71% with very practical criterion. Student response was obtained from 12 students, and the questionnaire result was 84.64% with very good criterion.